Knowledge assets in services across industries and across time - G. Scott Erickson; Helen N. Rothberg (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
This paper explores the question of whether knowledge assets are more developed in services industries than in non-services. The concept of the 'knowledge economy' has always gone hand-in-hand with growth in the percentage of the economy represented by services. Two multi-year, multi-industry datasets are used to directly compare the knowledge asset levels in service industry firms against those in non-service industry firms. Service industries do, indeed, reflect higher levels of intellectual capital in recent years, but did not do so a decade ago. Further, there is considerable evidence of changes in specific service and non-service industries over the time period, adding details to the finding that knowledge development is not static but does vary over time and circumstance. These results open up a number of promising research directions that could lead to a better understanding of the nature of these differing circumstances and how better strategic choices might be made regarding investments in knowledge management.
Keywords: L8; O39; 330; Intellectual capital; Knowledge management; Knowledge assets; Tobin's q; Services